2021
DOI: 10.1038/s41598-021-97823-1
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous and gaseous plasma applications for the treatment of mung bean seeds

Abstract: Sprouts are particularly prone to microbial contamination due to their high nutrient content and the warm temperatures and humid conditions needed for their production. Therefore, disinfection is a crucial step in food processing as a means of preventing the transmission of bacterial, parasitic and viral pathogens. In this study, a dielectric coplanar surface barrier discharge (DCSBD) system was used for the application of cold atmospheric plasma (CAP), plasma activated water (PAW) and their combination on mun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 49 publications
(63 reference statements)
0
8
0
1
Order By: Relevance
“…The germination percentage reached up to 100% (from 94%) when plasma and PAW (CO 2 ) were used; however, the PAW generated using O 2 [PAW(O 2 )] inactivated more microorganisms than the other PAW. 79 Apart from germination enhancement, plasma also has the ability to change the minerals, pigments, enzymes, and other nutritional compositions of the seeds. For example, in capacitively coupled plasma (CCP) treated tomato seeds, calcium (7.73%) and boron (11.53%) contents were increased; 80 whereas in soybean, nutrient fractions such as soluble protein and soluble sugar and enzymes such as peroxidase (POD) and phenylalanine ammonia-lyase (PAL) activities increased aer CDPJ treatment.…”
Section: Plasma Treatment Of Seeds/plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The germination percentage reached up to 100% (from 94%) when plasma and PAW (CO 2 ) were used; however, the PAW generated using O 2 [PAW(O 2 )] inactivated more microorganisms than the other PAW. 79 Apart from germination enhancement, plasma also has the ability to change the minerals, pigments, enzymes, and other nutritional compositions of the seeds. For example, in capacitively coupled plasma (CCP) treated tomato seeds, calcium (7.73%) and boron (11.53%) contents were increased; 80 whereas in soybean, nutrient fractions such as soluble protein and soluble sugar and enzymes such as peroxidase (POD) and phenylalanine ammonia-lyase (PAL) activities increased aer CDPJ treatment.…”
Section: Plasma Treatment Of Seeds/plantsmentioning
confidence: 99%
“…The germination percentage reached up to 100% (from 94%) when plasma and PAW (CO 2 ) were used; however, the PAW generated using O 2 [PAW(O 2 )] inactivated more microorganisms than the other PAW. 79…”
Section: Plasma Applications In Pre-harvest Stagesmentioning
confidence: 99%
“…Sprout seeds are the primary contaminants for an enclosed sprout production line to contaminate the final sprout before packaging and distribution ( Darmanin et al, 2021 ). Sprout seeds require warm and humid conditions for germination ( NACMCF., 1999 ); macromolecules containing nutrient substances will be released during germination to facilitate the growth of surrounding bacteria ( Yang et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Their nutrients, especially isoflavone, and selenium biofortification, are notably improved due to germination [ 4 , 5 ]. However, soybean sprouts are particularly prone to microbial contamination due to their high nutrient content and the warm temperatures and humid conditions needed for their production [ 3 , 6 ]. Various studies have demonstrated that the germination step is the main source of microbial contamination, with 3.0–6.0 log CFU/g microbes in sprouts, which are 2 or 3 logs greater than those observed outside sprouts [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%